The Association Between Neuropathological Lesions and Body Mass Index Is Independent of Cognitive Abilities. - Ururahy, Raul Dos Reis; do Val, Marina Scott; Ciciliati, Aline Maria Macagnan; Leite, Renata Elaine Paraizo; Paes, Vitor Ribeiro; Rodrigues, Roberta Diehl; Grinberg, Lea Tenenholz; Pasqualucci, Carlos Augusto; Jacob Filho, Wilson; Suemoto, Claudia Kimie (J Alzheimers Dis, 2024)
BACKGROUND: The association of moderate and severe dementia with low body mass index (BMI) is well described, but weight decline seems to also occur in individuals with preclinical neuropathologies. Considering that up to one-fifth of individuals with normal cognition meet the criteria for a dementia-related neuropathological diagnosis, autopsy studies are key to detecting preclinical neurodegenerative and cerebrovascular diseases that could be underlying weight changes. OBJECTIVE: We investigated the association between dementia-related brain lesions and BMI and evaluated whether the cognitive function was a mediator of this association. METHODS: In 1,170 participants, sociodemographic data, clinical history, and cognitive post-mortem evaluation were assessed with an informant. Neuropathological evaluation was performed in all cases. Linear regression models were used to investigate the association between neuropathological lesions (exposure variable) and BMI (outcome) adjusted for demographic, clinical, and cognitive variables in the whole sample, and in only those with normal cognition. Corrections for multiple comparisons were performed. In addition, a mediation analysis was performed to investigate the direct and indirect effects of cognitive abilities on the association between neuropathology and BMI. RESULTS: Individuals with lower BMI had a higher burden of neuropathological lesions and poorer cognitive abilities. Only neurofibrillary tangles (NFT) and neuropathological comorbidity were associated with low BMI, while other neurodegenerative and cerebrovascular lesions were not. NFT were indirectly associated with BMI through cognitive abilities, and also directly, even in participants with normal cognition. CONCLUSIONS: Neurofibrillary tangles were directly associated with low BMI even in individuals with preclinical Alzheimer's disease.

Diabetes is Not Associated with Alzheimer's Disease Neuropathology. - Dos Santos Matioli, Maria Niures Pimentel; Suemoto, Claudia Kimie; Rodriguez, Roberta Diehl; Farias, Daniela Souza; da Silva, Magnólia Moreira; Leite, Renata Elaine Paraizo; Ferretti-Rebustini, Renata Eloah Lucena; Farfel, José Marcelo; Pasqualucci, Carlos Augusto; Jacob Filho, Wilson; Arvanitakis, Zoe; Naslavsky, Michel Satya; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Previous evidence linking diabetes to Alzheimer's disease (AD) neuropathology is mixed and scant data are available from low- and middle-income countries. OBJECTIVE: To investigate the association between diabetes and AD neuropathology in a large autopsy study of older Brazilian adults. METHODS: In this cross-sectional study, diabetes was defined by diagnosis during life or use of antidiabetic medication. A standardized neuropathological examination was performed using immunohistochemistry. The associations of diabetes with Consortium to Establish and Registry for Alzheimer Disease (CERAD) scores for neuritic plaques and Braak-Braak (BB) scores for neurofibrillary tangles were investigated using multivariable ordinal logistic regression. We investigated effect modification of education, race, and APOE on these associations. RESULTS: Among 1,037 subjects (mean age = 74.4±11.5 y; mean education = 4.0±3.7 y; 48% male, 61% White), diabetes was present in 279 subjects. Diabetes was not associated with BB (OR = 1.12, 95% CI = 0.81-1.54, p = 0.48) or with CERAD (OR = 0.97, 95% CI = 0.68-1.38, p = 0.86) scores on analyses adjusted for sociodemographic and clinical variables. We observed effect modification by the APOE allele ɛ4 on the association between diabetes mellitus and BB scores. CONCLUSION: No evidence of an association between diabetes and AD neuropathology was found in a large sample of Brazilians; however, certain subgroups, such as APOE allele ɛ4 carriers, had higher odds of accumulation of neurofibrillary tangles.